Internet connectivity disruption in Nepal (Nepal) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Nepal. Data sourced from IODA.
Network Disruption Incident ID: NP-2026-0038. Severity: critical. Confidence: 65%